Automated apparatus for separating a biological sample from a two dimensional electrophoresis gel - MICHEL SAMUEL; ANDERSON N. LEIGH; GOODMAN JACK (2002)
An automated high-throughput system for excising spots or samples from an electrophoresis slab gel includes a computer controlled robotic arm assembly and a sample plate handling assembly for supplying a sample plate to a loading station. The computer is connected to a scanner and imaging device to identify selected sample locations on the slab gel and to direct the robotic arm to the selected locations for excising the gel spots. The cutting assembly includes a removable tray for supporting the slab gel during the cutting process and is coupled to the automated sample plate handling assembly. The sample plate handling assembly delivers a multiwell plate to the cutting assembly for receiving the gel spots. The removable tray cooperates with a scanner for identifying protein spots and includes a positioning device to position the tray in the scanner and the cutting assembly in selected locations to coordinate the scanned image with the cutting process.